Project for a Scientific Sociology - Casser, Joan, (Social Sciences E-Books Online, Collection 2025, 2025)
Cessante causa, cessat effectus (when the cause ceases, the effect ceases) is applicable for every existing type of social pathology. In Project for a Scientific Sociology , Joan Casser provides an operational overview of inter-individual behavior. He develops the research of Scottish physicist James Clerk Maxwell, Russian neurologist Ivan Pavlov, Swiss psychiatrist Eugen Bleuler, et al., as a means to examine energy transference in society. Prediction, motion, operant conditioning, crime, punishment, security, and law-governed behavior are reviewed socio-logically. Casser commences with worked matter and ends with the state in this causal configuration of inter-individual behavior.